Effects of Different Liquid Smoke Flavor Levels on the Shelf Life of Venus Clam (Chamelea Gallina, L 1758) Meat - Alcicek, Zayde (Wiley, 2014)
This study investigated the effects of smoke flavoring (SF) on vacuum-packed and chilled Venus clam meat shelf life. The different levels of SF led to different TVB-N (total volatile basic nitrogen), TVC (total viable count), LAB (lactic acid bacteria), pH and sensory evaluations during 30 days of storage (P<0.05). SF had no effect on moisture, protein, lipid and ash contents of Venus clams during storage. The addition of 200mL of SF per liter of 4% brine solution was preferred because of its sensory attributes, microbial and chemical characteristics, and 30-day shelf life at refrigerated storage. Practical Applications The present experiment demonstrates that the addition of SF highly affected the shelf life of liquid smoked clams. The maximum shelf life of the LS2 group was determined as 30 days. Our results showed that the addition of 200mL/L SF to 4% brine solution provided the best results for consumer acceptance, as well as microbial and chemical properties for Venus clam.
Keywords: Salmon Salmo-Salar; Polycyclic Aromatic-Hydrocarbons; Anchovy Engraulis-Encrasicolus; Pah Content; Quality; Fillets; Improvement; Pressure; Mackerel; Yield